2006
DOI: 10.1242/dev.02269
|View full text |Cite
|
Sign up to set email alerts
|

Somite-derived cells replace ventral aortic hemangioblasts and provide aortic smooth muscle cells of the trunk

Abstract: We have previously shown that endothelial cells of the aortic floor give rise to hematopoietic cells, revealing the existence of an aortic hemangioblast. It has been proposed that the restriction of hematopoiesis to the aortic floor is based on the existence of two different and complementary endothelial lineages that form the vessel: one originating from the somite would contribute to the roof and sides, another from the splanchnopleura would contribute to the floor. Using quail/chick orthotopic transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
126
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 61 publications
16
126
1
1
Order By: Relevance
“…Furthermore it was suggested that it may also give rise to smooth muscle cells. The somitic origin of smooth as well as endothelial cells in the dorsal aorta was recently demonstrated in the chick embryo (Pouget et al 2006). Using a retrospective clonal analysis in the mouse embryo, based on the rare intragenic recombination of a LaacZ sequence to give a functional LacZ reporter, we have shown that the smooth muscle of the dorsal aorta has a common clonal origin with the skeletal muscle of the myotome (Esner et al 2006).…”
Section: Smooth Muscle Cells Derived From Pax3 Expressing Paraxial Mementioning
confidence: 93%
“…Furthermore it was suggested that it may also give rise to smooth muscle cells. The somitic origin of smooth as well as endothelial cells in the dorsal aorta was recently demonstrated in the chick embryo (Pouget et al 2006). Using a retrospective clonal analysis in the mouse embryo, based on the rare intragenic recombination of a LaacZ sequence to give a functional LacZ reporter, we have shown that the smooth muscle of the dorsal aorta has a common clonal origin with the skeletal muscle of the myotome (Esner et al 2006).…”
Section: Smooth Muscle Cells Derived From Pax3 Expressing Paraxial Mementioning
confidence: 93%
“…Clonal analyses in the chick indicates that single cells in somites give rise to endothelial clones in the limb (Kardon et al 2002) while in mouse, it was shown that angioblasts leaving somites are committed to the endothelial lineage (Esner et al 2006;Pouget et al 2006;Sato et al 2008;Ohata et al 2009;Yvernogeau et al 2012). Altogether, these results strongly suggest that cells expressing VEGFR2 in somites are committed angioblasts.…”
Section: Genetic Control Of Vll Differentiationmentioning
confidence: 94%
“…The sclerotome along with mesenchymal cells from the somitocoel gives rise to the axial cartilage, tendons, and bones, while the remaining epithelial dorsal compartment of the somite is referred to as the dermomyotome. As its name indicates, the dermomyotome gives rise to the dorsal dermis and the primitive skeletal muscle, as well as smooth muscles of the aorta, lymphatic, and vascular endothelial cells (Wilting and Becker 2006;Esner et al 2006;Pouget et al 2006;Yusuf and Brand-Saberi 2006).…”
Section: Muscle Formationmentioning
confidence: 99%
See 2 more Smart Citations